Pathways to synergize reductive with relational logics in environmental policy - Katharina-Victoria Pérez-Hämmerle; Katie Moon; Christopher M. Raymond; Patrick Lucas; Viola Hakkarainen; Penney Wood (Ecosystems and People)
Transformative policies and policy instruments that effectively and equitably address climate change, biodiversity loss and social-ecological inequality are essential. This paper examines how environmental policy can better integrate reductive with relational logics to accommodate diverse worldviews and improve conservation outcomes. We argue that current approaches are largely defined by reductive logics that function to separate, isolate and objectify – to simplify – and could be improved through the integration of relational logics that encapsulate complexity via the conceptualization of dynamic interconnectivity and interdependence. To do so, we explore how time, space, and entities are conceptualized differently under reductive and relational logics. We illustrate these concepts through multiple cases including: market-based instruments such as biodiversity offset markets, legislative changes to World Heritage Convention Criteria and the Te Urewera Act of 2014 in Aotearoa New Zealand. Our analysis reveals the potential of relational logics to transform environmental policy, leading to more inclusive, culturally appropriate, and effective governance strategies. We propose four key practices for navigating towards a plurality of logics in policymaking: 1) recognizing different logical frameworks and adapting language and metrics; 2) accounting for power dynamics; 3) embracing culturally appropriate co-construction; and 4) contextualizing social-ecological systems with place-based knowledge. We conclude by discussing future directions for policy development in environmental governance, emphasizing the need for ongoing experimentation, evaluation, and refinement in the practical implementation of relational logics in policy.